2004
DOI: 10.1103/physrevb.69.155206
|View full text |Cite
|
Sign up to set email alerts
|

Structure, energetics, and extrinsic levels of small self-interstitial clusters in silicon

Abstract: Native defects in Si are of obvious importance in microelectronic device processing. Self-interstitials in particular are known to mediate, in many cases, anomalous impurity diffusion. Here we study the energetics and electronic structure of single, double, and triple self-interstitial clusters in crystalline Si in various charge states and geometries, providing extrinsic levels and binding-association-dissociation energies. We discuss the comparison of our results with some experimental data on self-implanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 35 publications
5
39
1
Order By: Relevance
“…We have used an energy cutoff of 550 eV and a 4 × 4 × 4 Monkhorst-Pack [28] Γ-centered k-point mesh for (i), (ii) and (iii) calculations. This simulation setup results in a denser k-point mesh [14] and larger energy cutoff [15,16] than previous studies. For (iv) calculations, we have used an energy cutoff of 150 eV and a 2x2x2 Monkhorst-Pack Γ-centered k-point mesh due to computational restrictions as we included 600 empty bands in the calculation.…”
Section: Simulation Detailsmentioning
confidence: 95%
See 3 more Smart Citations
“…We have used an energy cutoff of 550 eV and a 4 × 4 × 4 Monkhorst-Pack [28] Γ-centered k-point mesh for (i), (ii) and (iii) calculations. This simulation setup results in a denser k-point mesh [14] and larger energy cutoff [15,16] than previous studies. For (iv) calculations, we have used an energy cutoff of 150 eV and a 2x2x2 Monkhorst-Pack Γ-centered k-point mesh due to computational restrictions as we included 600 empty bands in the calculation.…”
Section: Simulation Detailsmentioning
confidence: 95%
“…They concluded that the W PL line was due to I 3 -I as I 3 -V did not introduce electronic states in the semiconductor gap. In contrast, Lopez et al did not find enough evidences to associate I 3 -I to the W line due to its high formation energy and the bad agreement of its donor level with the photon energy of the W line [15,16]. With respect to the X line, Carvalho et al suggested the tetra-interstitial Si cluster configuration proposed by Arai et al as X PL center, despite that its donor level did not agree with experimental values, and there were some discrepancies of the calculated LVMs with experiments [17].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Another possible reason might be the additional energy states due to the interstitial silicon atoms 27 in the channel, as interstitial silicon atoms can be injected from the oxidation front into silicon beam structure during the thermal oxidation process. 28 The model suggests that interstitial silicon atoms near the oxide/channel interface injected by sacrificial oxidation and following gate oxidation processes, which generated energy states near conduction band edge that evaluated in this letter.…”
mentioning
confidence: 99%